Effect of Technological Change on Economic Growth in the Eastern Economic Corridor: The Case Study of Chonburi Province, Thailand - Kasrisom, Arnon (Journal of Applied Economics and Management Strategy, 2024)
The purpose of this research is to study the technological changes in Chonburi Province that affect its economic growth and analyze the factors determining those changes. Historical annual data from 1993 to 2022 are used in the quantitative analysis along with an econometric model in the form of a complex multiple regression equation. The findings of this study reveal that technological change has had a positive impact on the economic growth of Chonburi Province, with the total economic sector achieving 0.0142% with differences in each production sector. However, the production sector exhibited the highest rate of technological change, notably within the utilities, mining, and sanitation sectors. This was followed by commerce, the handicraft industry, warehouse transit, and the transportation sectors. The agriculture, forestry, hunting, and fishery sectors, as well as the metal and non-metallic mining sectors, followed respectively. However, the manufacturing sector, along with the public construction-repair and demolition sector experienced change in the negative direction. In terms of the factors affecting the change in growth of the economic sector as a whole and every branch of production, capital factors were found to have a greater effect than labor factors. When analyzing the influence of factors that determine technological change, each production sector experienced different effects. Research and development expenditure at the national level was found to have the most significant relationship in the same direction as the factors promoting investment in Chonburi Province. In contrast, a significant relationship in the opposite direction was revealed with the value of output not only in the economic sector as a whole but also in each sector of production. Therefore, this research provides recommendations to the government and related agencies by highlighting the necessity for workers with a high level of education. Besides technology development, national value of machinery imported from abroad in each production sector should be emphasized to harness benefits and supporting foreign direct investment and domestic entrepreneurs.